COMPARATIVE ANALYSIS OF CHINESE AND UZBEK MUSICAL ART - Amirjonova Charos Qobiljon qizi; Valiyeva Noiba Abbasxonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article provides a comparative analysis of the historical development of the musical arts of Uzbekistan and China, their connection with various musical instruments and cultural information. Both nations reflect their cultural heritage through their unique melodies, traditional national music and performance styles. While maqoms, folklore and folk tunes play a large role in Uzbek musical art, classical music and imperial court music play an important role in Chinese music.